Automated information retrieval theory and methods - Shapiro, Jacob; Voiskunskii, Vladimir G. (Academic Press, 1997)
Automated Information Retrieval describes a fully automated Boolean System and gives special attention to theoretical problems in automatic retrieval of textual information. The book details algorithms in each process in the system, including those that are radically new in the retrieval process and those that are adaptable to the individual. New approaches to evaluating information retrieval systems and studying their performance are included. This book reviews the general principles of constructing any system, such as an information retrieval system. It provides a detailed analysis of basic concepts such as information need, information, information crisis, and the notation of information retrieval. It examines the goal, function, structure, and language of an information retrieval system. It describes the construction of an information retrieval system (methods, algorithms, and approaches). It details different approaches to evaluating the results of information retrieval. It features new directions in the development of information retrieval systems.
Keywords: Database management.; Information storage and retrieval systems.; elektronické knihy; electronic books